Inflorescences of Cliffortia L. (Rosaceae) and related vegetative branching patterns - A. C. Fellingham (Bothalia: African Biodiversity & Conservation, 2003)
The inflorescence construction of eight species, representative of the types found in the 119 species of the rosaceous genus Cliffortia L. is described, based on stereo microscopic examination of fresh and dried specimens, combined with extensive field observations. In its simplest form the inflorescence is a reduced short shoot, bearing a lateral ebracteate flower and a potentially viable apical bud. Variations in the basic structure can be in the number of flowers, the mix of the sexes of the flowers and the number and type of short shoots as primary, secondary and tertiary axes. A high incidence of structural plasticity of the inflorescence occurs. This can be either throughout the development of the inflorescence or only at the onset of the vegetative stage. These changes occur in the short shoot(s) constituting the axes of the inflorescence, causing either an increase in the length of the intemodes. apical proliferation of the axes or a combination of these two effects. A specific combination of changes is linked to a specific inflorescence type. The vegetative elements of the inflorescence thus modified, are retained as an integral part of the vegetative branching system, with extensive influence on the branching pattern. This can also result in the predominance of one sex over the other over time, so that an individual, initially of the one sex. can become one of the opposite sex by the end of the season. Erroneous interpretation of a single point in the process of sex change as if it is a permanent state of sexuality, led to the prev alent acceptance of dioecy as the norm for the genus. Monoecy with dichogamy (or herkogamy at inflorescence level) was observed in this genus, as in many other wind-pollinated taxa.